Strengthening regional integration/cooperation with the Neighbourhood System of Innovation conceptual framework: the case of China and ASEAN - Tang, Ming Feng; Baskaran, Angathevar; Yan, Hui; Muchie, Mammo (Taylor & Francis, 2015)
Traditional neo-classical market approach to regional integration/cooperation mainly focuses on trade and investment. The paper proposes an innovation system approach to regional integration/cooperation as an alternative that focuses on knowledge, learning, innovation, and competence (KLIC) building without excluding trade and investment. The underlying argument is that while liberal trade and investment conceptual framework takes a narrow economic gain and loss approach, the system of innovation approach includes economic and non-economic variables by including KLIC, and broad economic and social gain. The paper presents the Neighbourhood System of Innovation (NeSI) conceptual framework which captures the reciprocal interactions between national innovation systems (NSI) of larger ‘regional economic pole’ (REP) and smaller economies (or among NSIs of the smaller economies) in the ‘Neighbourhood’ region. The case of China and Association of Southeast Asian Nations (REP and Neighbourhood, respectively) is used to demonstrate the usefulness of NeSI framework and its possible application to other similar cases. The aim of the paper is not to produce a path-breaking theory, but to present a different perspective through innovation systems approach as an alternative to enhance understanding of regional integration and cooperation dynamic processes.